2017
DOI: 10.1002/anie.201708693
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Arylamines via Aminium Radicals

Abstract: Arylamines constitute the core structure of many therapeutic agents, agrochemicals, and organic materials. The development of methods for the efficient and selective construction of these structural motifs from simple building blocks is desirable but still challenging. We demonstrate that protonated electron‐poor O‐aryl hydroxylamines give aminium radicals in the presence of Ru(bpy)3Cl2. These highly electrophilic species undergo polarized radical addition to aromatic compounds in high yield and selectivity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 88 publications
2
61
0
Order By: Relevance
“…These results demonstrated that TFAand Sc(OTf) 3 were helpful for promoting the oxidation of the thioamide substrate and in the meanwhile avoiding overoxidation of the heterocyclic product. [18] In the reaction mixture,T FA probably undergoes ligand exchange with Sc(OTf) 3 to generate stronger acid TfOH, which increases the concentration of the protonated form (II). One-electron anodic oxidation of the thioamide substrate I leads to the formation of the thioamidyl radical cation II, [17] which is in equilibrium with the neutral thioamidyl radical III.R adical cyclization followed by oxidative rearomatization afford the final product V.T he cyclization via II is expected to be more efficient than the neutral species III because the S-radical in II is more electrophilic than that in III,a nd thus more reactive toward the phenyl ring.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrated that TFAand Sc(OTf) 3 were helpful for promoting the oxidation of the thioamide substrate and in the meanwhile avoiding overoxidation of the heterocyclic product. [18] In the reaction mixture,T FA probably undergoes ligand exchange with Sc(OTf) 3 to generate stronger acid TfOH, which increases the concentration of the protonated form (II). One-electron anodic oxidation of the thioamide substrate I leads to the formation of the thioamidyl radical cation II, [17] which is in equilibrium with the neutral thioamidyl radical III.R adical cyclization followed by oxidative rearomatization afford the final product V.T he cyclization via II is expected to be more efficient than the neutral species III because the S-radical in II is more electrophilic than that in III,a nd thus more reactive toward the phenyl ring.…”
mentioning
confidence: 99%
“…Briefly,t he substituent on the thioamide nitrogen atom tolerated iPr (15), Cy (16), and tBu (17). Substrates bearing electron-rich and electrondeficient phenyl rings all reacted smoothly to afford the desirable N,S-heterocycles (18)(19)(20)(21)(22)(23)(24)(25)(26). Besides the methanesulfonyl (Ms) group, p-tulenesulfonyl (Ts; 27)a nd acyl groups (28-33)were suitable substituents on the nitrogen linker.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthers alternatives were developed by Liu and co‐workers starting from aryl azides, Sanford and co‐workers who started from phthalimide trifluoroacetamides instead of pyridinium triflates yielding aryl phthalimides and by Leonori and co‐workers who started from O ‐dinitroaryl hydroxylamines yielding arylamines (e.g. piperidines) . In addition to this method, Leonori and co‐workers recently contributed another procedure for the direct amination of arenes starting from simple, unfunctionalized secondary amines …”
Section: C–n Bondmentioning
confidence: 99%
“…Continuing this line of investigation, we have recently identified conditions for the preparation of aryl amines from electron‐poor O ‐aryl hydroxylamines ( 43 , Ar=2,4‐(NO 2 ) 2 ‐C 6 H 3 ) . In this case, the strong Bronsted acid HClO 4 was required to access the highly electrophilic aminium radicals.…”
Section: Addition To Aromaticsmentioning
confidence: 99%